2019
DOI: 10.1002/lsm.23175
|View full text |Cite
|
Sign up to set email alerts
|

Single Ablative Fractional Resurfacing Laser Treatment For Forearm Actinic Keratoses: 6‐Month Follow‐Up Data From An Intrapatient Comparison Between Treated and Untreated Sites

Abstract: Background and Objectives: Actinic keratoses (AK) are common pre-cancerous lesions, which are associated with ultraviolet light exposure and aging. Wounding therapies such as fractionated laser resurfacing (FLR) have been previously demonstrated to effectively treat facial AK. However, the effectiveness of FLR on other sites commonly afflicted with AK has not been studied in detail. Previously, our group has reported that treatment of aged skin with wounding therapies including dermabrasion and ablative frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Throughout the current 36 month follow-up period, this ratio has been maintained; in fact, none of the ratios determined at 3, 6, 12, 18, 24, 30, or 36 months post-FLR are significantly different. As described in our first report on this cohort, these data indicate FLR is an effective treatment for existing AKs (15). However, our model predicts that FLR treatment will also prevent the occurrence of new AK lesions.…”
Section: Akssupporting
confidence: 70%
See 2 more Smart Citations
“…Throughout the current 36 month follow-up period, this ratio has been maintained; in fact, none of the ratios determined at 3, 6, 12, 18, 24, 30, or 36 months post-FLR are significantly different. As described in our first report on this cohort, these data indicate FLR is an effective treatment for existing AKs (15). However, our model predicts that FLR treatment will also prevent the occurrence of new AK lesions.…”
Section: Akssupporting
confidence: 70%
“…As this is an ongoing study, the number of return visits by subjects is also shown in Table 1. We have previously reported outcomes for of these subjects at 3 and 6 months following FLR treatment (15). Subsequent to that report, 18 additional subjects have been recruited to the study.…”
Section: Aksmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in pol g lead to a variant form of the skin cancer-prone disease xeroderma pigmentosum (XP-V) (33), and thus, the lower expression of pol g protein in sunlight-exposed geriatric skin may explain the elevated risk of skin cancer in these individuals. Interestingly, skin rejuvenation approaches such as fractionated laser resurfacing demonstrated the ability to restore IGF-1 expression in geriatric skin to levels found in young adult skin (8,19,20,55) and may prevent the development of actinic keratoses (56). Thus, it will be interesting to determine whether these clinical interventions similarly restore the capacity for proper p53 signaling in the skin of older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, novel treatments aimed for geriatric patients both predisposed and exposed to NMSC have been developed. One such modality is wounding therapy, which attempts to reverse the geriatric fibroblast senescence phenotype by inducing a "wounding response" (19)(20)(21)(22)(23). This effectively serves to rejuvenate geriatric skin to a more youthful phenotypic and constitutive expression.…”
Section: Introductionmentioning
confidence: 99%